PENGARUH ANTENATAL PERINEAL MASSAGE PADA PRIMIGRAVIDA TERHADAP LASERASI PERINEUM SAAT PERSALINAN DI KOTA SEMARANG TAHUN 2017 - Erna Kusumawati; Agustin Rahmawati; Siti Istiana (Universitas Muhammadiyah Semarang, 2017)
rauma of the birth canal is closely related to labor. It is also related to the morbidity and mortality rate of the mother. The birth process is almost 90% of those with perineal rupture, either with or without an episiotomy. Antenatal Prenatal Massage performed at the gestation period of ≥34 weeks can reduce the incidence occurring in labor or postpartum. The purpose of this study was to see the effectiveness ofantenatal perineal massage on the degree of perineal laceration. The method used in achieving these goals using comparative or difference test with two different sample groups of pregnant women given perineal massage treatment of 45 people and the control group is pregnant women who are not given any treatment as much as 45 people. The results of the study there were significant differences between degree of perineal laceration between treatment group and control group at the end of measurement.Keywords: Perineal Laseration, Antenatal Perineal Massage, Primigravid